2021
DOI: 10.1016/j.jvir.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular Intrahepatic Portosystemic Shunt Creation for the Prevention of Gastric Variceal Rebleeding in Patients with Hepatocellular Carcinoma: A Multicenter Retrospective Study

Abstract: Purpose: To evaluate the effectiveness and safety of transjugular intrahepatic portosystemic shunt (TIPS) creation for the prevention of gastric variceal rebleeding in patients with hepatocellular carcinoma (HCC). Materials and Methods:This multicenter retrospective study included 126 cirrhotic patients (mean age, 54.1 ± 10.2 years; 110 men) with HCC who underwent TIPS creation for the prevention of gastric variceal rebleeding. Of these, 110 (87.3%) patients had gastroesophageal varices and 16 (12.7%) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Better liver function, that is, lower Child‐Pugh Score, absence of macrovascular invasion, solitary or smaller HCCs (<3 cm) and ALBI score were among the factors linked to better survival. Death was attributed predominantly to liver failure and tumour progression, and liver transplantation rate, was reported in only two studies from 1.6% to 5.9% 14,24 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Better liver function, that is, lower Child‐Pugh Score, absence of macrovascular invasion, solitary or smaller HCCs (<3 cm) and ALBI score were among the factors linked to better survival. Death was attributed predominantly to liver failure and tumour progression, and liver transplantation rate, was reported in only two studies from 1.6% to 5.9% 14,24 …”
Section: Resultsmentioning
confidence: 99%
“…All 11 studies (Table 1 ) were retrospective of low to medium quality (Supplementary Table 1 ) and in total included 937 patients, 870 of which with TIPS placement after the diagnosis of HCC to treat the complications. 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Most studies originated from China and the majority had hepatitis B virus‐associated cirrhosis and/or alcohol‐related disease. Patients were mostly male (range: 57.9%–100%) and the mean age ranged from 46.3 to 63.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the American Association for the Study of the Liver (AASLD) and Society of Interventional Radiology (SIR) Guidelines, extensive primary or metastatic malignancy is a relative contraindication to TIPS due to a perceived risk of complications such as shunt occlusion and hemorrhage (13,14). Multiple studies have reported the utility of TIPS in the setting of cirrhosis with concomitant hepatocellular carcinoma (HCC) (14)(15)(16)(17)(18)(19)(20)(21). Minimal data exists on TIPS for the treatment of pseudocirrhosis secondary to extensive non-HCC hepatic malignancy.…”
Section: Introductionmentioning
confidence: 99%